The Contrastive Move Analysis: An Investigation of Persian and English Research Articles’ Abstract and Introduction Parts - Vakili, Elham Zand; Kashani, Alireza Fard (Richtmann Publishing, 2012)
The study of the generic and rhetorical structure of the research article genres and sub-genres is of crucial importancein academic writing investigations. While the majority of such studies have mostly focused on articles written in English, theanalysis of the ‘moves’ in other languages might shed some light on cultural and linguistic variations in functional levels. Thepresent study investigated ten Persian and English Linguistics articles in terms of their moves in abstract and introduction parts.Analysis was conducted by incorporating Hyland’s (2000) Information-Purpose-Methods-Products-Conclusion (IPuMPrC) modeland Swales’ (1990) the CreateAResearchSpacemodel (CARS) for abstract and introduction parts, respectively. Findingsrevealed that while the moves mentioned by Hyland (2000) and others are totally typical to English research articles, somesignificant variations exist in Persian articles.